S = 9 − 9 1 3 + 8 1 1 3 − 6 5 6 1 1 3 + 4 3 0 4 6 7 2 1 1 3 − . . . . . . .
If S = b a where a , b are both primes, find a + b .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Awesome question! You combined 2 infinite nested radicals methods into 1! :D
excellent solution!!!!
that moment when I thought of I=4! true happiness! :)
Nice solution :) I did the same! Does anyone happen to know of a more 'economical' method for solving quartics however? My method is much too long-winded!
Log in to reply
For example, how did you know there was a solution of A=0.5(sq.rt(53)-1)?
a⁴-26a²+a+156=0 i.e. (a-4)(a³+4a²-10a-39)= (a-4)(a+3)(a²+a-13)=0 so a=(-1±√53)/2 OR YOU CAN FACTOR F(a)=a⁴-26a²+a+156 Put a=10, 7566=6 1261=6 13 97 Because 156=3 52=13*12 97+3=100 or 97+13=110 97=10²-3 or 97=10²+10-13 Now just check a⁴-26²+a+156 is divided by a²+a-13 Notist 6=10-4,13=10+3
S = 9 − 3 1 1 3 + 1 3 − 1 3 + 1 3 + …
Let 1 3 + 1 3 − 1 3 + 1 3 + … = x
also, let 1 3 − 1 3 + 1 3 + … = y
then, we see that
1 3 + y = x ( 1 )
and
1 3 − x = y ( 2 )
squaring both ( 1 ) and ( 2 ) and subtract to get:
y + x = x 2 − y 2 = ( x + y ) ( x − y ) 1 = x − y ⟹ y = x − 1
Substitution y = x − 1 to ( 1 ) , we have x 2 − x − 1 2 = 0 . So, we have x = 4 and x = − 3 . But, since S is positive, then x should be positive, so x = − 3 is discarded.
Finally, S = 9 − 3 1 × 4 = 3 2 3
and, the required answer is 2 3 + 3 = 2 6
Did Ramanujan had something to with this expression for S? I instantenously thought of him when i saw this problem
Problem Loading...
Note Loading...
Set Loading...
We can write the expression as S = 9 − 3 A ,
where A = 1 3 + 1 3 − 1 3 + 1 3 − 1 3 + . . . . . .
Now ( A 2 − 1 3 ) 2 = 1 3 − A , which by observation has A = 4 as a solution. (There is another positive solution, namely A = 2 5 3 − 1 , but since this value is less than 1 3 it can be discarded.)
So S = 9 − 3 4 = 3 2 3 ,
and thus a + b = 2 3 + 3 = 2 6 .